Irritable bowel syndrome – modern ways of treatment - Kuciński, Jakub; Fryska, Zuzanna; Wołejko, Adam; Kulik, Kacper; Semeniuk, Paweł; Matusz, Krystian; Burczyk, Rafał; Górna, Natalie (Journal of Education, Health and Sport, 2023)
Introduction Irritable bowel syndrome (IBS) is the most frequent functional disorder of the gastrointestinal tract. Main symptoms are recurring stomach ache connected with defecation, changes of frequency of defecation and/or stool’s consistency. Cause of IBS is still unknown unlike its pathomechanism. Continuous research allows doctors to understand and treat it better. Discussion Diagnosing IBS might be difficult even for the most experienced doctors due to its uncharacteristic symptoms. Therefore diagnosis should be made by using Rome IV Criteria. IBS is divided into 4 subtypes basing on clinical picture: IBS with predominant constipation, IBS with predominant diarrhea, IBS with mixed bowel habits and IBS unclassified. Classification is being performed with the use of Bristol Stool Chart. Choice of remedy should be made depending on the subtype of IBS. Pharmacological treatment is symptomatic and focuses on relieving pain, diarrhea, constipation and bloating. Drugs that can be used are: loperamide, rifaximin, antispasmodic (e.g. hyoscine), antidepressants or laxatives. Treatment should also contain nonpharmacological methods. Nonpharmacological techniques which are proved to help patients contain regular physical activity, body mass reduction, low-FODMAP diet, using probiotics, psychotherapy and supplementing soluble fibre. Conclusions IBS is a big issue for public health as it is lowering quality of life and is generating big indirect costs. Difficulties in diagnosing are increasing those costs. That’s why it is of high importance to find more effective therapy. Raising awareness among doctors is crucial as plenty of methods are available to treat the disease which allows to reduce symptoms and costs.